Quality of life of young male catheterized patients - Pramanik, Sandip; Kumar Paul, Uttam; Kumar Pal, Dilip (International Journal of Medical Research and Review, 2018)
Introduction: It is pointless to point out that, Per-urethral or Supra-pubic Catheter compromises the Quality of life (QoL) of young male patients. Our study is about the comparison of QoL status along with depression of catheterized state with same after removal of catheter of patients. Objectives: In our study we wanted to quantify the quality of life (QoL) and distress experienced by patient following catheterisation and also to assess the improvement of QoL after catheter removal following surgical intervention. Methods: We used two tools named World Health Organization Quality of Life scale (WHOQOL BREF) and Beck Depression Inventory (BDI) for this purpose. Result: We found statistically significant improvements in all domains of QoL as measured by WHOQOL BREF and improvement in depression status as well, measured by Beck Depression Inventory (BDI). Conclusion: As we have documented poor QoL and depression status in catheterised state and improvement of the same after catheter removal we recommend counselling of such patients regarding QoL and Psychiatry consultation for management of depression.